Impact of natremia on metastatic non small cell lung cancer patients receiving immune checkpoint inhibitors - Martina Catalano; Sara Fancelli; Enrico Caliman; Francesca Mazzoni; Marta Gatta Michelet; Silvia Mancini; Clara Manneschi; Sonia Shabani; Brunella Napolitano; Serena Pillozzi; Lorenzo Antonuzzo; Giandomenico Roviello (Scientific Reports)
Abstract Hyponatremia has been established as a prognostic indicator of survival in metastatic non-small cell lung cancer (mNSCLC). Conversely, the influence of normal sodium levels remains unexplored. This study aims to investigate the impact of natremia in mNSCLC patients undergoing treatment with immune checkpoint inhibitors (ICIs). Clinical and biochemical data of patients treated with ICIs for mNSCLC were obtained. Availability of baseline sodium values was a study inclusion criterion. Patients were categorized into two groups based on the cut off sodium value, determined using the receiver operating characteristic curve. Subsequently, the influence of sodium levels on response rate (RR), disease control rate (DCR), progression-free survival (PFS), and overall survival (OS) was analyzed. PFS and OS were assessed via the Kaplan–Meier method. Univariate and multivariate Cox regression analyses were conducted to evaluate prognostic factors for PFS and OS. The analysis included 88 patients, of whom 73.1% were men, with a median age of 71 years (range, 47–91). A comparison between patients with baseline natremia ≥ 140 mEq/L (n = 43) and those with < 140 mEq/L (n = 45) revealed PFS durations of 7.0 vs. 2.1 months (p < .01) and OS durations of 15.6 vs. 6.8 months, respectively (p = .02). In the univariate survival analysis, pre-ICI serum sodium ≥ 140 mEq/L (p = .01) was associated with improved PFS, while factors associated with OS included brain metastasis (p = .05) and pre-ICI serum sodium ≥ 140 mEq/L (p = .02). In the multivariate analysis, pre-ICI serum sodium ≥ 140 mEq/L maintained a statistically significant association with OS (p = .04)..This study represents the first investigation into the impact of normonatremia in mNSCLC. Our findings suggest that serum sodium levels < 140 mEq/L at baseline and initial assessment are independently associated with poorer PFS and OS in mNSCLC patients undergoing first-line treatment with ICIs.